VITAMIN C FACILITATES DOPAMINE NEURON DIFFERENTIATION IN FETAL MIDBRAIN THROUGH TET1- AND JMJD3-DEPENDENT EPIGENETIC CONTROL MANNER - He, Xi-Biao (Stem Cells, 2015)
Intracellular Vitamin C (VC) is maintained at high levels in the developing brain by the activity of sodium-dependent VC transporter 2 (Svct2), suggesting specific VC functions in brain development. A role of VC as a cofactor for Fe(II)-2-oxoglutarate-dependent dioxygenases has recently been suggested. We show that VC supplementation in neural stem cell (NSC) cultures derived from embryonic midbrains greatly enhanced differentiation towards midbrain-type DA (mDA) neurons, the neuronal subtype associated with Parkinson’s disease. VC induced gain of 5-hydroxymethylcytosine (5hmC) and loss of H3K27m3 in DA phenotype gene promoters, which are catalyzed by Tet1 and Jmjd3, respectively. Consequently VC enhanced DA phenotype gene transcriptions in the progenitors by Nurr1, a transcription factor critical for mDA neuron development, to be more accessible to the gene promoters. Further mechanism studies including Tet1 and Jmjd3 knockdown/inhibition experiments revealed that both the 5hmC and H3K27m3 changes, specifically in the progenitor cells, are indispensible for the VC-mediated mDA neuron differentiation. We finally show that in Svct2 knockout mouse embryos, mDA neuron formation in the developing midbrain decreased along with the 5hmC/ H3k27m3 changes. These findings together indicate an epigenetic role of VC in midbrain DA neuron development.